Effects of external loads on postural sway during quiet stance in adults aged 20–80 years. (January 2018) - Hill, M.W.; Duncan, M.J.; Oxford, S.W.; Kay, A.D.; Price, M.J.
Abstract: The purpose of this study was to investigate the effects of holding external loads on postural sway during upright stance across age decades. Sixty-five healthy adults (females, n = 35), aged 18–80 years were assessed in four conditions; (1) standing without holding a load, holding a load corresponding to 5% body mass in the (2) left hand, (3) right hand and (4) both hands. The centre of pressure (COP) path length and anteroposterior and mediolateral COP displacement were used to indirectly assess postural sway. External loading elicited reductions in COP measures of postural sway in older age groups only (P < 0.05). No changes were observed in younger or intermediate aged adults (P > 0.05). Holding external loads during standing is relevant to many activities of daily living (i.e. holding groceries). The reduction in postural sway may suggest this type of loading has a stabilising effect during quiet standing among older adults. Highlights: We examine decade changes in postural sway while holding loads in the hands. Postural sway decreased as a result of holding a light external load in older age groups. Holding loads attenuates the increase in postural sway often observed with older age. Although relevant to daily life, such tests may have limited diagnostic value.